Intercultural Communication: Acculturation, Assimilation and Problems - Suhardi; Rani; T Lembong Misbah (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2019)
As a cultured human being, it certainly requires communication, as for the communication that is established, namely intercultural communication. Singkil sub-district has a variety of ethnic groups, languages and different cultures, the tribes in the area are Javanese, Acehnese, Singkil tribe, Jamee / Minang tribe and Nias tribe. The object of research is the Singkil tribe and the Jamee / Minang tribe, because among the tribes in Singkil District the most dominant are the two tribes, so that the differences of opinion between the two. Therefore, this research was conducted to examine how Acculturation, Assimilation and also Enculturation exist in these two tribes, especially in Singkil District, and what are the problems or problems between the two tribes. The type of research used is qualitative research, the data collection techniques used are: observation in the field, interviews, and documentation, the respondents are the people of the two tribes in Singkil District. The results of this study prove that the Minang people find it difficult to understand the language of the Singkil tribe so that there are differences of opinion and perception between the two.